THE IMPLICATIONS OF TRADITIONAL SAGI BOXING ON STUDENTS' PHYSICAL FITNESS: A PHENOMENOLOGICAL STUDY - Bile, Robertus Lili; Ola Tapo, Yohanes Bayo; Dopo, Fransiskus Solanus (Universitas Labuhanbatu, 2025)
Purpose – This study aimed to explore students' experiences of traditional Sagi boxing practices and examine their implications for physical fitness. The research background is based on the low level of physical fitness among Indonesian students and the need for local wisdom-based innovations in physical activity.Methodology – The study employed an exploratory mixed-methods design with an emphasis on the phenomenological approach. Qualitative data were collected through in-depth interviews, participatory observation, and documentation of students actively practicing Sagi boxing in So'a Sub-district. Quantitative data were obtained through physical fitness measurements using the Indonesian Student Fitness Test.Findings – Students interpreted Sagi boxing not only as a cultural tradition but also as a physical activity that benefits fitness and mental balance. TKSI data indicated that the majority of participants' physical fitness fell within the fair to good category.Contribution – This study concludes that Sagi traditional boxing has excellent potential as an alternative activity to support students' physical fitness while preserving local culture. The findings provide a foundation for integrating traditional sports into physical education curricula.